2022
DOI: 10.1093/sleep/zsac181
|View full text |Cite
|
Sign up to set email alerts
|

Down syndrome: orofacial pain, masticatory muscle hypotonia, and sleep disorders

Abstract: The aim of the present study was to investigate orofacial pain in individuals with Down syndrome (DS) and determine possible associations with masticatory muscle hypotonia (MMH), maximum mouth opening (MMO), and sleep disorders. Twenty-three individuals with DS underwent a standardized clinical examination using Axis I of the Diagnostic Criteria for Temporomandibular Disorders, for the diagnosis of pain in the masseter and temporal muscles and temporomandibular joint (TMJ). MMH was investigated using electromy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…It has been found that men with Down syndrome more often suffer from myofascial pain, muscle hypotonia, obstructive sleep apnea, and snoring. Women with DS, on the other hand, report joint pain and SB more often [29]. The hypermobility characteristic of Down syndrome also confirms the problem with disorders of the temporomandibular joints and their excessive mobility, which is manifested by cracking in the joint and malocclusion [7].…”
Section: Discussionmentioning
confidence: 75%
“…It has been found that men with Down syndrome more often suffer from myofascial pain, muscle hypotonia, obstructive sleep apnea, and snoring. Women with DS, on the other hand, report joint pain and SB more often [29]. The hypermobility characteristic of Down syndrome also confirms the problem with disorders of the temporomandibular joints and their excessive mobility, which is manifested by cracking in the joint and malocclusion [7].…”
Section: Discussionmentioning
confidence: 75%
“…Obstructive sleep apnea (OSA) is a prevalent sleep issue among DS patients, with an almost 100 % prevalence rate in adolescent and adult patient populations [ 15 ]. Furthermore, pediatric DS populations often experience bedtime resistance, sleep anxiety, night awakenings, disrupted sleep patterns, and excessive daytime somnolence [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Тригеминокардиальный рефлекс может возникать при надавливании на глазные яблоки, во время операционных процедур, в том числе в периорбитальной области, при резекции опухолей в области моста и мозжечка, а повреждение проекций афферентной иннервации в области верхней и нижней челюсти повышает вероятность снижения уровня артериального давления, развития брадикардии, асистолии, апноэ во время бодрствования, а также усиливает перистальтическую функцию желудочно-кишечного тракта [4,5]. Поскольку центростремительные нервы в составе тригеминоспинального солитарного тракта от лицевой области способны активировать ноцицептивные соматовисцеральные и висцеро-висцеральные рефлексы, характерная для повышенной возбудимости системы тройничного нерва циркуляция возбуждения по замкнутому кругу проявляется различными дисфункциями: невралгией тройничного нерва, лицевыми болями, мигренеподобными состояниями, бруксизмом [5,6]. Причем сонный бруксизм как более интенсивная форма ритмической активности жевательных мышц в 8 % случаев сопровождается остановкой работы сердца [3].…”
unclassified